Efektivitas Manajemen Pengalihan Tenaga Kependidikan SMA dan SMK Pada UPTD Pusat Pengembangan Mutu Guru - Cut Muftia Keumala; Zanzibar Zanzibar; Zahara Fonna (Sekolah Tinggi Ilmu Administrasi Nasional, 2019)
This study aims to determine the effectiveness of the management of the transfer of educational personnel under the provincial government along with its obstacles. The results revealed that 463 educators were teaching at 10 public SMA including 2 private SMA in Lhokseumawe city, Aceh, Indonesia. Besides, 325 educators teaching at 13 State Vocational High Schools including 3 private SMK, and 276 non-PNS educators who teach at 10 SMA and 13 SMK. The conclusion is that the management of the transfer of education personnel under the provincial government has not been realized effectively, because there are still various obstacles, including personnel administration processes such as teacher certification, teacher promotion and provision of teacher allowances as well as increasing teacher resources (HR) through an increasingly long bureaucratic process. Apart from that, non-civil servant educators who have had a less than satisfying fate, because there is no clarity and certainty about their future destiny. Efforts made are the socialization of Law Number 23 of 2014 concerning Regional Government and the management of BKN Number 1 of 2016 concerning the transfer of educators to the Provincial Government. Other efforts include improving personnel administration services (teacher certification, promotion and determination of educational personnel allowances for teachers) as well as taking policies to clarify the status and honorarium/salary of non-PNS teachers.